Investigation of channel-encased braces incorporating circular HSS. (1st March 2021) - Seker, Onur; Shen, Jay; Faytarouni, Mahmoud; Akbas, Bulent
Highlights: Comprehensive survey of tested circular hollow shape specimens was conducted. Experimental study is carried out on small-scale isolated brace specimens. Effectiveness of the developed channel-encased bracings are investigated in terms of inelastic cyclic behavior and fracture life. Experimental and numerical investigations showed that the channel-encased bracings are promising. Abstract: Ductile concentrically braced frames (CBFs) with circular hollow shapes (CHS) have been one of the most common structural systems in seismic regions and are expected to undergo significant inelastic deformations mainly through post-buckling or yielding deformations in their bracing members. However, a comprehensive survey of the experimentally tested CHS specimens carried out in the course of this study indicated that there exists a discrepancy between the expected demand and capacity of conventional CHS bracings. To overcome this quantitatively identified inconsistency, which might result in a poor performance under severe ground shakings, a new and simple performance-enhancing method is proposed and examined. The developed improvement technique, which can be implemented in both new and existing steel buildings, is employed by encasing a CHS bracing in two channels connected with welded stitches. Experimental and numerical investigations into the effectiveness of the developed system showed that the developed channel-encased bracings are promising in terms of improving the cyclic stability and cumulative energy dissipation capability compared with the conventional bracings.